Pediatric and youth traffic-collision injuries in Al Ain, United Arab Emirates: a prospective study. - Michal Grivna; Hani O Eid; Fikri M Abu-Zidan (PLoS ONE, 2013)
AIM: To study the mechanism of road traffic collisions (RTC), use of safety devices, and outcome of hospitalized pediatric and youth RTC injured patients so as to give recommendations regarding prevention of pediatric RTC injuries. METHODS: All RTC injured children and youth (0-19-year-olds) who were admitted to Al Ain City's two major trauma centers or who died after arrival to these centers were prospectively studied from April 2006 to October 2007. Demography of patients, road-user and vehicle types, crash mechanism, usage of safety devices, injured body regions, injury severity, Revised Trauma Score, Glasgow Coma Scale, intensive care unit admissions, hospital stay and mortality were analyzed. RESULTS: 245 patients were studied, 69% were vehicle occupants, 15% pedestrians, 9% motorcyclists and 5% bicyclists. 79% were males and 67% UAE citizens. The most common mechanism of RTC was rollover of vehicle (37%) followed by front impact collision (32%). 32 (13%) of vehicle occupants were ejected from car. 63% of ejected occupants and 70% of motorcyclists sustained head injuries. Only 2% (3/170) vehicle passengers used seatbelts and 13% (3/23) motorcyclists a helmet. CONCLUSIONS: Male drivers and UAE nationals were at high risk of RTC as drivers and as motorcyclists. Ejection rate was high because safety restraint use was extremely low in our community. More education and law enforcement focusing especially on car/booster seat use is needed.